Changes in bioactive compounds' stability and colour of functional plum spread during different storage conditions - Bajić Aleksandra R.; Mastilović Jasna S.; Cvetković Biljana R.; Kovač Renata M.; Ubiparip-Samek Dragana N.; Djordjević Marijana Z.; Djordjević Miljana Z.; Dragojlović Danka M. (Food and Feed Research)
There is growing interest in utilizing juice pomace, including plum pomace, in new food products as a sustainable strategy for reducing agro-waste. As an alternative source of dietary fibres and phenolic bioactives, plum pomace represents a valuable ingredient in functional food development. Some phenolics, such as anthocyanins are more sensitive and susceptible to degradation processes in fruit preparation during storage. This study aimed to assess the effect of a storage period and temperature on the retention of phenolics, anthocyanins (total and monomeric) and the colour of functional plum spread enriched with plum pomace. The spreads were stored at 4°C (14 days) and 20°C or 40°C for 14, 28 and 45 days. The control sample was also analysed one day after production and measurements for investigated spreads were compared. Results revealed that total phenolics remained more stable than total anthocyanins and monomeric anthocyanins at room temperature, while a temperature of 40°C led to the loss of all bioactives. Refrigeration of spread was found to significantly slow down the loss of phenolics and anthocyanins and better preserve colour. Colour deterioration was observed in all samples, with the least change at 4°C.